Scanning Electron Microscope Study of the Root-knot Nematode (Meloidogyne incognita) on Tomato Root - Wergin, W P (Journal of nematology, 1981)
This study examines the types of structural information that can be gained by utilizing the scanning electron microscope (SEM) and a cryofracture technique to examine the host-parasite interaction. Roots of tomato, Lycopersicon esculentum cv. Marglobe, were cultured aseptically and inoculated with the root-knot nematode, Meloidogyne incognita. Twenty-four hours to four weeks after inoculation, developing galls were removed from the cultures and processed for SEM observation. The cryofracture technique was used to reveal internal structural features within the developing galls. The results illustrate structural details concerning penetration of the roots, differentiation of syncytia, and development of the nematodes beginning with the second-stage larvae and ending with adult egg-laying females